Conservative treatment of penile carcinoma - a retrospective study of 10 years - Neide Pereira; Ana Rita Cabral; Ricardo Vieira; Americo Figueiredo (Sociedade Brasileira de Dermatologia, 2013)
Conservative treatment of penile squamous cell carcinoma has been advocated as a method of choice for tumours at early stages. Thirty patients with a mean age of 63.2 years were treated with CO2 laser ablation, radical local excision with preputial flap, direct closure or healing by secondary intention, circumcision alone or associated with CO2 laser and topical imiquimod. Sixteen patients had local recurrence. Partial penectomy was necessary in 3 patients. Conservative treatments of penile squamous cell carcinoma in early stages (< T1a) do not seem to compromise the survival rate, so it may be advisable for this subset of patients.